Appropriate CT cervical spine utilisation in the emergency department - Cassie Jaeger; Mark Baker; Carol Hafley; James Waymack (BMJ Open Quality, 2020)
Introduction Over 40 000 CT scans are performed in our emergency department (ED) annually and utilisation is over 80% capacity. Improving medical appropriateness of CT scans may reduce total number of scans, time, cost and radiation exposure.Methods Lean Six Sigma methodology was used to improve the process. A National Emergency X-Radiography Utilisation Study (NEXUS)-based PowerForm was implemented in the electronic health record and providers were educated on the criteria.Results The rate of potentially medically inappropriate CT C-spine scans decreased from 45% (19/42) to 22% (90/403) (two-proportion test, p=0.002). After the intervention, there was no longer a difference between midlevel providers and physicians in the rate of medically inappropriate orders (19% vs 22%) (two-proportion test, p=0.850) compared with that before the intervention (56% vs 31%) (two-proportion test, p<0.01). Overall rates of CT C-spine scans ordered decreased from 69.3 to 62.6/week (t-test, p=0.019).Conclusion A validated clinical decision-making tool implemented into the medical record can improve quality of care. This study lays a foundation for other imaging studies with validated support tools with similar potential improvements.